A representação da infância em Ponciá Vicêncio. - Santos, Fernanda Nunes dos (2018)
For a long time, blacks were discriminated against and had to undergo various actions of the white, given the context of slavery. Through this reality, this study seeks to analyze, from the black and female voices, the representation of childhood in the work "Ponciá Vicencio", Conceição Evaristo, with the purpose of reflecting on the inexistence of childhood in the twelfth century. Brazil as a slave country, after the year 1850, was composed of children, grandchildren, great-grandchildren and tetranetos of slaves, mainly Africans. In this way the children are represented so as to look like domestic animals, at the table of lords, taking food scraps. From this scenario, an analysis was carried out through the deepening of the character Ponciá Vicencio, from his childhood to his adult life, since in the work the representation of childhood is performed from the protagonist. For that, we start from the concept of childhood proposed in Ariés (1973) and Lima Vieira (2010), among other authors, who base our analysis. In analyzing the work, we perceive the figuration of the social space of childhood in this novel, which ends up using the aestheticization of memory, with the intention of placing the black child on the scene and presenting the child, symbolizing the history of a collective black Brazilian people.